The Application of Statistical Regression for Geographical Data Analysis - Priyono, P (Forum Geografi, 1997)
Application of regression statistic to analyse geography data is getting familiar, as the reason that geography object is really wide, kwantitative approach of geography and availibilty computer software of regression analysis which is getting complete and refresentative. The way of making decision and prediction constitutes the superiority of regression analysis and constitutes the issue which is often met by geographer in the study of geography object. It not only phenomena of human geography, but phisycal geography phenomena is also able to be approtached by regression analysis. For user the attentions that ought to be noticed are 1) regression statistic ought to be appraised as a fool and not as a brain, so that researcher is the main important operator; 2) mastery of geography subject matter constitutes an essential basis; 3) statistic is able to work if there is a detum which is able to fulfill the term of requirements and preceded by a logic causal relation; 4) close attention of reasearcher is highly required; 5) when must, researcher use theÂ statistic and the relationship between data type and statistical technique.